Determinants of occupancies and patterns of the multicultural societies at the urban mosque open spaces in Kuala Lumpur, Malaysia - Nizarudin, Norhanis Diyana; ,; , (UTM, 2019)
Mosques are recognised as physical representations of Islam and its cultural distinctiveness in Malaysia. The novel notion of the mosques suggests that its function as a public place should be all-inclusive, not only for Muslims but also to instigate the participation of other society members. Apart from emphasising the mosques’ built architectural elements, the idea of exploring the inclusive occupancies of the mosque open spaces is believed to be highly significant. Alongside the far-reaching studies conducted on the utilisation of open spaces, this study intends to identify the determinants of spatial occupancies of the open spaces by the multicultural societies at the national, district and sub-district urban mosques in Kuala Lumpur. Through systematic observations with behaviour mapping, this method lends itself to an investigation of the usage-spatial relationship of open spaces in the forms of behavioural patterns based on certain intervals of time and narrative information. A few spatial determinants were identified – the location of the urban mosques, the spatial layout of the studied open spaces, the design and conditions of landscape features, as well as the allocation of facilities and amenities. Besides, sociocultural determinants were also identified from the observations and conversations with users which include – the heterogeneity of users and their interactions, the physical and social activities happening in and around the open spaces, as well as users’ preferences and motivations for utilising the spaces. Based on the identified determinants, improvements on the existing urban mosque open spaces design are required in fostering better multicultural participation and engagement.